Ectoparasite assemblage of the four-striped mouse, Rhabdomys pumilio : the effect of anthropogenic habitat transformation and temporal variation - Van der Mescht, Luther (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScConsEcol)--University of Stellenbosch, 2011.